The Contribution of Global Transport on North American Carbon Monoxide Concentrations - Ehlers, Susanna (My University, 2007)
Carbon monoxide, CO, is produced by natural and anthropogenic processes including biomass burning and fossil fuel usage and affects atmospheric chemistry through its roles as a sink for the hydroxyl radical (OH) and as a precursor to ozone. As the primary atmospheric sink for OH, which is responsible for chemically destroying numerous air pollutants, CO concentrations impact the concentrations of other such pollutants. Here we use CO as a tracer for polluted air masses by examining the transport of CO both to and from North America. CO is an ideal tracer for atmospheric and climate modeling because it is well understood and well captured due to its simple chemistry and long lifespan. By employing MOZART, a numerical global tropospheric chemistry model, we seek to address the nature of air pollutant transport and establish the role of transport on regional North American CO concentrations. We find that the greatest intercontinental transported CO occurs on days when the overall carbon monoxide concentrations are low to moderate. In addition, carbon monoxide concentrations increase eastward, reflecting the different regional impacts of emissions. We also define three main transport pathways of CO over North America and identify specific episodic flux events by comparing model results to INTEX-NA flight observations taken the summer of 2004 in cooperation with NASA, NOAA, and the ICARn campaign. The main pathways of CO transport over North America are eastward, aloft import from Asia; northward, surface import from Africa, attributed to heavy biomass burning in the summer; and eastward export from North America, at the surface and aloft. Understanding these pathways for CO transport and the regional impacts is a key step towards understanding how polluted air masses evolve and can provide insight into the extent to which local air quality is influenced by intercontinental transport.
Keywords: Carbon Monoxide